PENANAMAN MORAL AGAMA PADA ANAK MELALUI CERITA BERNUANSA ISLAMI - Nur Kholis; Putri Ferawati (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2021)
This article aims to describe the cultivation of religious morals in children through stories with Islamic nuances. The method used in this research is descriptive qualitative, data was taken using interviews, observation and documentation. The results of this study indicate that the use of stories with Islamic nuances can increase the moral values of religion in children. This is evidenced by students who are able to speak politely to teachers and their peers, students begin to show a responsible attitude and students also begin to show an honest attitude. The positive contribution of this research is to provide information to the wider community, especially in the field of education that the use of Islamic nuanced story methods can increase religious moral values in children.